2022
DOI: 10.3390/jpm12050719
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Patient-Specific Integrated Education Program on Pain, Perioperative Anxiety, and Functional Recovery following Total Knee Replacement

Abstract: The perioperative care of patients undergoing total knee arthroplasty (TKA) affects functional recovery and clinical outcomes. This study aims to introduce a patient-specific integrated education program (IEP) into the TKA clinical pathway and to evaluate patient outcomes between the intervention and control groups. We performed a two-site, two-arm, parallel-prospective controlled trial. The experiment group received an IEP incorporating verbal preoperative education, prehabilitation, multidisciplinary persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…One trial did not report separate outcomes for hip and knee arthroplasty, 47 and in another study the reviewers were unable to obtain the raw data sets. 48 Therefore, 20 trials were included in the meta-analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One trial did not report separate outcomes for hip and knee arthroplasty, 47 and in another study the reviewers were unable to obtain the raw data sets. 48 Therefore, 20 trials were included in the meta-analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…the reviewers were unable to obtain the raw data sets. 48 Therefore, 20 trials were included in the meta-analysis (Figure 1). Study characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Medina-Garzon [19] evaluated the effectiveness of a nursing intervention with three sessions of motivational interviewing to reduce preoperative anxiety in patients who underwent TKA and reported that anxiety levels improved after the intervention. Ho et al [20] introduced a patient-speci c integrated education program into the TKA clinical pathway and reported that anxiety status improved after the intervention regarding STAI scores during hospitalization. This study evaluated anxiety levels before and after intervention in the same patients and indicated that anxiety levels signi cantly decreased after intervention compared with those before intervention.…”
Section: Effectiveness Of Preoperative Interventionmentioning
confidence: 99%